Uniform Error Bounds for Reconstruct Functions from Weighted Bernstein Class - Peixin Ye; Yongjie HAN (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Errors appear when the Shannon sampling series is applied to reconstruct a signal in practice. This is because the sampled values may not be exact, or the sampling series may have to be truncated. In this paper, we study errors in truncated sampling series with localized sampling for band-limited functions from weighted Bernstein class. And we apply these results to some practical examples. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3078